Le Japon selon Chris Marker - Emi Koide (Appareil)
This article focuses on the status of Japan, as a place where memory, imagination, time and space are related – a space of alterity and displacement – in Marker’s works, specifically: Le mystère Koumiko (1965), Sans Soleil (1982), Le Dépays (1982), Level Five (1997). This treatement aims to analyse how these works depicted post-war Japan – afflicted by collective amnesia and the by presence of media images.